2019
DOI: 10.1002/aoc.4829
|View full text |Cite
|
Sign up to set email alerts
|

MAO‐free and extremely active catalytic system for ethylene tetramerization

Abstract: The original Sasol catalytic system for ethylene tetramerization is composed of a Cr source, a PNP ligand, and MAO (methylaluminoxane). The use of expensive MAO in excess has been a critical concern in commercial operation. Many efforts have been made to replace MAO with non‐coordinating anions (e.g., [B(C6F5)4]−); however, most of such attempts were unsuccessful. Herein, an extremely active catalytic system that avoids the use of MAO is presented. The successive addition of two equivalent [H(OEt2)2]+[B(C6F5)4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
(94 reference statements)
0
14
0
Order By: Relevance
“…Preparation of the catalyst precursors discussed in a previous work. [46] 4 ] À (1.0 eq), CrCl 3 (THF) 3, and 2 were mostly soluble in methylcyclohexane. The methylcyclohexane-soluble portion (92 wt%) was taken by filtration for the use in the oligomerization studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preparation of the catalyst precursors discussed in a previous work. [46] 4 ] À (1.0 eq), CrCl 3 (THF) 3, and 2 were mostly soluble in methylcyclohexane. The methylcyclohexane-soluble portion (92 wt%) was taken by filtration for the use in the oligomerization studies.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the reactor was fully filled with PE when the oligomerization was performed with the Cr-complex prepared with 1 bearing no À SiR 3 substituents (i. e., [1-CrAlCl 3 (acac) (THF)] + [B(C 6 F 5 ) 4 ] À ). [46] By lowering the reaction temperature, the 1-octene/1-hexene ratio increased accordingly, reaching 67/16 at a temperature of 60°C (entries 3-6). When methylcyclohexane solvent was replaced with toluene, the activity was significantly reduced to 1200 kg/g-Cr/h.…”
Section: Full Papersmentioning
confidence: 98%
See 1 more Smart Citation
“…CrCl 3 (thf) 3 has been actively used as a component of the ethylene tetramerization catalyst system [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. We also developed a very efficient catalyst for ethylene tetramerization ( Scheme 1 ) [ 35 , 36 , 37 ]. The catalyst shows extremely high activity (~5000 kg/g-Cr/h) and is advantageous over other reported systems in that it works with an inexpensive activator, iBu 3 Al, avoiding the use of expensive MAO in excess (A1/Cr = 300–500) [ 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both PNP and PPN molecules possess many conformations, and analysis of the wrong conformer will result in incorrect ΔG PPN . A previous DFT study of PNP ligand conformers found variation of up to 9.9 kcal/mol in calculated Gibbs free energy 25 , which would drastically impact any thermodynamic comparison with PPN isomer.…”
mentioning
confidence: 97%